Ulasan Berbasis Maslahah terhadap Fatwa MUI tentang Cryptocurrency: Perspektif Manusia yang Sadar - Sanuri Sanuri; Masdar Hilmy; Nafi’ Mubarok; Imroatul Azizah; Yoga Irama; Hidayatulloh Hidayatulloh (Universitas Islam Negeri Antasari Banjarmasin, 2025)
Cryptocurrency is increasingly gaining global popularity, particularly among investors and digital entrepreneurs. In parallel, debates surrounding its permissibility under Islamic law have intensified. The lack of legal clarity among Islamic scholars presents a significant challenge in providing normative guidance. The fatwa issued by the Indonesian Ulema Council (MUI) declaring cryptocurrency haram (unlawful) has drawn criticism for being misaligned with contemporary concepts of maslahah and the evolving digital economy. This study critically examines the MUI's prohibition through the lens of Al-Tufi's human cognition-based theory of maslahah alongside contemporary Muslim scholars who assess legal rulings through contextual considerations of harm (mafsadah) and benefit (maslahah). This research is a literature-based study employing a normative-juridical approach and qualitative analysis, exploring the fatwa through the principles of Islamic jurisprudence, maslahah, and maqasid al-shari'ah while drawing on both classical and contemporary Islamic thought. The findings reveal that the MUI fatwa, based on four legal grounds—gharar (speculation), darar (harm), qimar (gambling), and sil'ah (tradable commodity)—and a rigid textual approach, fails to incorporate a human cognition-based maslahah as a viable alternative to support regulatory clarity and an adaptive formulation of Islamic law responsive to digital innovation. The study recommends prioritizing regulatory and constitutional certainty to enable a more adaptive and progressive Islamic legal response to technological advancement.